Description and results of birth defects surveillance and follow‐up programs in Bogotá and Cali, Colombia, 2002–2019. Issue 3 (6th January 2021) - Zarante, Ignacio; Carreño‐Martinez, Angie Carolina; Ibañez, Lina Maria; Gracia, Gloria; Blandón, Esperanza; Perez, Gladys; Holguín, Jorge; Hurtado‐Villa, Paula
Abstract: Birth defects are structural or functional defects present at birth and are caused by different factors that affect intrauterine development. They are the second most common cause of death under five years of age in Latin America and the Caribbean. In Bogotá and Cali, Colombia, there are two surveillance programs established to evaluate the prevalence of them. The purpose of the following article is to describe the experience and results of the surveillance of the Birth Defects Surveillance Programs in Bogotá and Cali, Colombia, 2002‐2019. The information was taken from the surveillance programs that have an active hospital system in some institutions of the city (ECLAMC modality), and use data from the passive national system (Sistema Nacional de Vigilancia en Salud Pública ‐ SIVIGILA) to expand their coverage. From 2002 until 2019, 1, 289.650 births have been monitored through one of the surveillance programs, including both methodologies. The importance of surveillance programs relies on the amount of data obtained that allows the development of research, the detection of potential changes throughout time, and the guidance of public policies to improve promotion and prevention strategies.